The level of awareness for paying zakat on jewellery gold: A study in Kota Bharu, Kelantan / Nur Aisah Aina Mohamad Nafi - Mohamad Nafi, Nur Aisah Aina (Academy of Contemporary Islamic Studies, 2018)
The social scenario is unclear about the law of gold zakat jewelry, as well as the existence of fatwa in non-uniform countries about it. This study aims to identify the gold zakat jewelry payment of law and to analyze the level of awareness of the Muslim community on the payment of gold zakat jewelry. The main method used in this study was the method of questionnaire with descriptive analysis and a total of 103 questionnaires were distributed to respondents consisting of women in Kota Bharu. This study is useful for students in particular zakat institutions to empower and improve the collection and distribution of zakat.